TELKOM GROUP'S BLOCKING OF NETFLIX AS A BASIS FOR IDENTIFYING INDICATIONS OF UNFAIR BUSINESS COMPETITION: A STUDY OF KPPU DECISION NO. 08/KPPU-I/2020 - Nurdin, Merry Kurniawati; Sakti, Muthia (International Journal of Cultural and Social Science, 2025)
This study analyzes unfair business competition practices in the telecommunications sector in Indonesia, which analyzes in more depth the case study of blocking carried out by PT Telekomunikasi Selular and PT Telekomunikasi Indonesia under the auspices of the Telkom Group against the Over The Top (OTT) service Netflix. The author uses a normative method with a case and legislative approach, this study found that the unilateral blocking carried out by the Telkom Group has fulfilled the elements of discrimination regulated in Article 19 letter (d) of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition because the Telkom Group only blocked Netflix, while other OTT services that have done the same thing were not subjected to the same blocking, in this case the Telkom Group's policy as a dominant business actor in the telecommunications sector also has a negative impact on consumer internet access. However, despite the discovery of discriminatory acts that are strong indications, the KPPU decision in Case No. 08 / KPPU-I / 2020 stated that the Telkom Group was not indicated in unfair business competition practices, this indicates a legal weakness. This legal weakness is caused by the non-implementation of the Network Neutrality principle in regulations governing the flow of telecommunications services and the limitations of business competition test indicators that cannot analyze the long-term impact (Network Effects) in the digital telecommunications market. Therefore, this study concludes that regulators must harmonize by improving regulations on cooperation between telecommunications services and OTT services through fair and transparent Business to Business principles, as well as adding long-term impact (Network Effects) test criteria to the KPPU Commission Regulation to ensure healthy competition in the future.